Role of statin as inducer of Hmox-1 system in treatment of preeclampsia - Putra, Ridwan A; Effendi, Jusuf S; Permadi, Wiryawan; Bandiara, Ria; Fauziah, Prima N (Cellular and Molecular Biology, 2018)
Preeclampsia is the major cause of both maternal and neonatal morbidity and mortality. Its insidence remains high and the management has not been established yet because its etiology and pathophysiological are still poorly understood. Theories regarding etiopathogenesis and management of preeclampsia have been postulated yet it remains controversial. Placental ischemic and angiogenic imbalance are suggested to be predisposing factors of preeclampsia. It is thereby targeted in prevention of preeclampsia. Unfortunately, both primary and secondary prevention using various supplements and drugs fails to exhibit good outcome. Overall, these efforts are considered useless. In recent years, researchers have been using statin derivative in management of preclampsia. It has been reported that statin provides protective effect in endothelial cells by inducing expression of Hmox-1 and inihibiting release of sFlt-1 as well as potent antioxidant properties. Thus, statin has been proposed as promising agent to significantly reduce anti-angiogenic in preeclamptic patients which is overviewed in this review based on recent studies.